Anaerobic Methane Oxidation in High-Arctic Alaskan Peatlands as a Significant Control on Net CH4 Fluxes - Kimberley E. Miller; Chun-Ta Lai; Randy A. Dahlgren; David A. Lipson (Soil Systems, 2019)
Terrestrial consumption of the potent greenhouse gas methane (CH4) is a critical aspect of the future climate, as CH4 concentrations in the atmosphere are projected to play an increasingly important role in global climate forcing. Anaerobic oxidation of methane (AOM) has only recently been considered a relevant control on methane fluxes from terrestrial systems. We performed in vitro anoxic incubations of intact peat from Utqiaġvik (Barrow), Alaska using stable isotope tracers. Our results showed an average potential AOM rate of 15.0 nmol cm3 h−1, surpassing the average rate of gross CH4 production (6.0 nmol cm3 h−1). AOM and CH4 production rates were positively correlated. While CH4 production was insensitive to additions of Fe(III), there was a depth:Fe(III) interaction in the kinetic reaction rate constant for AOM, suggestive of stimulation by Fe(III), particularly in shallow soils (<10 cm). We estimate AOM would consume 25–34% of CH4 produced under ambient conditions. Soil genetic surveys showed phylogenetic links between soil microbes and known anaerobic methanotrophs in ANME groups 2 and 3. These results suggest a prevalent role of AOM to net CH4 fluxes from Arctic peatland ecosystems, and a probable link with Fe(III)-reduction.